2023
DOI: 10.1021/acs.langmuir.3c00392
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Multicomponent Reactions-Directed Self-Assembled G-quadruplex Inherent Antibacterial Hydrogel

Abstract: Nowadays, inherent antibacterial hydrogels have gained significant attention due to their utilization against infectious bacteria. Herein, we focus on the development of an injectable, self-healable, dynamic, and G-quadruplex hydrogel with inherent antibacterial activity. The dynamic self-assembled hydrogel is constructed upon multicomponent reactions (MCR) among guanosine, 2-formylphenylboronic acid, and amino acid/peptides in the presence of potassium ions. The role of amino acid/peptides in the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 57 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…In recent years, a variety of wound dressings have been developed for treating wounds and promoting wound healing. Many functional wound dressings including electrospun nanofibers, biocompatible membranes, porous foams, and hydrogels have shown excellent antibacterial activities and healing-promoting abilities on bacterial-infected wounds. Among them, hydrogels with three-dimensional network porous structure, superior biocompatibility, and extracellular matrix-like microenvironment have attracted much attention and have been favored by many researchers. Hydrogels possess significant advantages in absorbing large amounts of tissue exudates, moisturizing and cooling wounds, relieving pain, and promoting wound healing. Moreover, hydrogels with antibacterial and bactericidal properties and injectable and self-healing capabilities are more suitable for the treatment of infected wounds because these types of hydrogels can not only promptly remove bacteria from infected wounds, eliminate wound inflammation, and reduce dressing change frequency, but they are also suitable for treatment of irregular wounds, promote and accelerate the healing of infected wounds, and have therefore been highly favored .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a variety of wound dressings have been developed for treating wounds and promoting wound healing. Many functional wound dressings including electrospun nanofibers, biocompatible membranes, porous foams, and hydrogels have shown excellent antibacterial activities and healing-promoting abilities on bacterial-infected wounds. Among them, hydrogels with three-dimensional network porous structure, superior biocompatibility, and extracellular matrix-like microenvironment have attracted much attention and have been favored by many researchers. Hydrogels possess significant advantages in absorbing large amounts of tissue exudates, moisturizing and cooling wounds, relieving pain, and promoting wound healing. Moreover, hydrogels with antibacterial and bactericidal properties and injectable and self-healing capabilities are more suitable for the treatment of infected wounds because these types of hydrogels can not only promptly remove bacteria from infected wounds, eliminate wound inflammation, and reduce dressing change frequency, but they are also suitable for treatment of irregular wounds, promote and accelerate the healing of infected wounds, and have therefore been highly favored .…”
Section: Introductionmentioning
confidence: 99%
“…To prevent secondary infection, various wound dressings such as foams, nanofibers, and hydrogels are used after trauma. Because of their restorability, biocompatibility, and resemblance to the extracellular matrix, hydrogels are the perfect dressing for the treatment of wound healing. Further, the water-swollen 3D polymer networks of hydrogels bestow the ideal environment for the suspension of nanoparticles . Das et al, have developed multicomponent reaction-directed nucleopeptide-coupled bioconjugated guanosine hydrogels which possess inherent antibacterial activity against both Gram-positive and Gram-negative bacteria. , Recent studies showed that an adhesive polymeric hydrogel could block the discharge of fluid and gas from the affected wound area, accelerating wound healing and preventing bacterial infections. Hydrogels blended with NO can be utilized for the treatment of wound healing, myocardial infection, and cancer. However, research exploring the application of an adhesive hydrogel and NO donor is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the functionality of phenylboronic acids and amphiphilic copolymers extends their use as nanoscale drug delivery systems. ,, However, studies on the toxicity and biocompatibility of PBA-based compounds have reported varying results. Therefore, the cytotoxicity and cell viability of these nanomaterials must be thoroughly evaluated before considering their practical applications in biomedical contexts. …”
Section: Introductionmentioning
confidence: 99%